Proportionality body and the relationship with the technique of preference of judoka - Saray Giovana dos Santos; Sebastião Iberes Lopes Melo; Cândido Simões Pires-Neto (Journal of Physical Education (Maringá), 2008)
The purpose of this study was to analyse the compatibility between Judo techniques and the body proportions of the athletes, taking into account: the "tokui-waza" technique, the mecanical aspects of the technique, the size of legs, trunk and acromium, besides the relationship between "tokui-waza" and the body proportions (size) according to Phanton. The sample was composed of twenty-two male, athletes whose average age was 18.9 years and whose average time of practice was 7.7 years. All subjects were measured according to Ross & Marfell-Jone's (1982) procedures. The Chi-quadractic test revealed no relationship between "tokui-waza" and size of legs, trunk and acromium. It may be concluded that the choise of "tokui-waza" does not depend on the size of these body segments.